Quatérnios, um ensaio sobre a regularidade e hiperperiodicidade de funções quaterniônicas, e o Teorema de Cauchy - Barreiro, Rodrigo Cardoso [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
O objetivo deste trabalho ée estabelecer similaridades entre a análise complexa e os quatérnios. Nele é feito um estudo da regularidade de funções quaterniônicas e são estabelecidas as funções exponencial e logarítmica para os quatérnios sendo feito um estudo da hiperpe- riodicidade dessas funções. Outro resultado apresentado é a generalização quaterniônica da fórmula integral de Cauchy um dos principais teoremas da análise complexa.

The objective of this work is to establish similarities between the complex analysis and the quaternions. In it is made a study of the regularity of quaternionic functions and are established the exponential and logarithmic functions for the quaternions being made a study of the hiperperiodicity of these functions. Another presented result is the quater- nionic generalization of the Cauchy's integral formula one of the main theorems of the complex analysis.
Keywords: Fisica matematica; Quaternios; Cálculo; Funções quaterniônicas; Cauchy, Teorema integral de; Hiperperiodicidade de funções quaterniônicas; Quaternions; Exponential e logarithmic quaternion functions; Hiperperi- odicity; Cauchy's integral formula for quaternions